Interaction between PAF and human platelet membranes: a fluorescence study - Ahmad Kantar; Pier Luigi Giorgi; Giovanna Curatola; Rosamaria Fiorini (Mediators of Inflammation)
The interaction between PAF and human platelet membranes was investigated by measuring the steadystate fluorescence anisotropy and fluorescence decay of 1 (4-trimethylammoniumphenyl)-6-phenyl-1,3,5-hexatriene (TMA-DPH) incorporated in platelet plasma membranes. PAF induced a time-limited and significant increase of the lipid order in the exterior part of the membrane and a decrease in membrane heterogeneity. These changes were blocked in the presence of the PAF antagonists, L-659,989 and 1-O-hexadecyl-2-acetyl-sn-glycero-3-phospho(N,N,N-trimethyl)hexanolamine.H2O. These results indicate that the observed changes in the physico-chemical properties of the membrane are attributed to the PAF–receptor interaction and signal transduction.